Stride characteristics progress in a 40-m sprinting test executed by male preadolescent, adolescent and adult athletes - Chatzilazaridis, I.; Panoutsakopoulos, V.; Papaiakovou, G. I. (Journal of Biology of Exercise, 2012)
The purpose of the present study was to examine the progress of sprint running velocity (SRV) during the acceleration and initial constant velocity phases in prepubescent (PPS), adolescent (ADS) and adult (AS) sprinters by comparing the progress of the magnitude of the stride length (SL) and stride frequency (SF). SRV, SL and SF progress for each 10-m interval of a 40-m sprinting test were examined with a video-analysis method for a total of thirty-one athletes. A 24 (age group 10-m interval) ANOVA with repeated measures on the second factor revealed that SRV was developed similarly in ADS and AS (p >.05) and it was differentiated (p < .05) in PPS due to the short in distance acceleration phase. Pearson's correlation analysis indicated that SRV and SL were highly correlated (r > .73, p < .05) for the entire distance of the sprinting test for AS and PPS. On the contrary, SF was the main contributor for SRV development in the 10-30m segment for ADS. In conclusion, SRV improvement seemed to be attributed to the increment of SL and SF, which were differently developed during the 40-m sprint performed by prepubertal, adolescent and adult sprinters.